The Effect of Internal Locus of Control, Human Resource Competence, and Financial Pressure on Fraud Prevention With Individual Morality as Moderator - Anisa Fitryanti; Amiruddin; Aini Indrijawati (Indonesian Journal of Business Analytics, 2023)
This study aims to examine the influence of internal locus of control, human resource competence, and financial pressure on fraud prevention with individual morality as a moderator. This study uses a quantitative approach by distributing questionnaires. The sample was selected through a purposive sampling technique of 110 respondents. This research was conducted in 25 SKPD Makassar city, the statistical method used to test the hypothesis was by using the Structural Equation Model (SEM), and the test was carried out using Smart-PLS 4.0. The results showed that internal locus of control, and human resource competence had a positive effect on fraud prevention, and financial pressure had a negative effect on fraud prevention. While the moderating effect in this study, individual morality strengthens the influence of internal locus of control, and human resource competence on fraud prevention, while individual morality weakens the effect of financial pressure on fraud prevention.